Isolated brachydactyly type E caused by a HOXD13 nonsense mutation: a case report - Jamsheer Aleksander; Sowińska Anna; Kaczmarek Leszek; Latos-Bieleńska Anna (BMC, 2012)
Abstract Background Brachydactyly type E (BDE; MIM#113300) is characterized by shortening of the metacarpal, metatarsal, and often phalangeal bones, and predominantly affects postaxial ray(s) of the limb. BDE may occur as an isolated trait or as part of a syndrome. Isolated BDE is rare and in the majority of cases the molecular pathogenesis has so far not been resolved. Originally, the molecular cause of isolated BDE has been unravelled in 2 families and shown to result from heterozygous missense mutations in the homeodomain of the HOXD13 gene. Since the initial manuscript, one further HOXD13 mutation has been reported only in a single family manifesting isolated BDE. Case Presentation In this paper, we report on a Polish family exhibiting isolated BDE caused by a novel nonsense heterozygous HOXD13 mutation. We investigated a Polish female proband and her father, both affected by isolated BDE, in whom we identified a nonsense heterozygous mutation c.820C > T(p.R274X) in the HOXD13 gene. So far, only two missense HOXD13 substitutions (p.S308C and p.I314L), localized within the homeodomain of the HOXD13 transcription factor, as well as a single nonsense mutation (p.E181X) were associated with BDE. Both missense changes were supposed to alter DNA binding affinity of the protein. Conclusion The variant p.R274X identified in our proband is the fourth HOXD13 mutation, and the second truncating (nonsense) mutation, reported to result in typical isolated BDE. We refer our clinical and molecular findings to the previously described HOXD13 associated phenotypes and mutations.